2019
DOI: 10.1007/978-3-030-27477-1_29
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Industrial Cyber-Physical System Deployed in an Automobile Multi-stage Production System

Abstract: Industrial Cyber-Physical Systems (CPS) are promoting the development of smart machines and products, leading to the next generation of intelligent production systems. In this context, Artificial Intelligence (AI) is posed as a key enabler for the realization of CPS requirements, supporting the data analysis and the system dynamic adaptation. However, the centralized Cloud-based AI approaches are not suitable to handle many industrial scenarios, constrained by responsiveness and data sensitive. Edge Computing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…For this purpose, according to the bibliographic search performed in the Scopus repository and considering the use of collective intelligence approaches to achieve the desired levels of autonomy and dynamic adaptation of industrial CPS, the main research works that directly propose collective-intelligence-based industrial CPS approaches were identified and analyzed, as summarized in Table 2. Framework that enables one to test the self-coordination of a swarm of controllers, aiming to solve the distributed optimal power flow algorithm in a DC network Queiroz et al, 2020 [26] Manufacturing system (tested in a real case study-automotive assembly line)…”
Section: Collective-intelligence-based Cps Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, according to the bibliographic search performed in the Scopus repository and considering the use of collective intelligence approaches to achieve the desired levels of autonomy and dynamic adaptation of industrial CPS, the main research works that directly propose collective-intelligence-based industrial CPS approaches were identified and analyzed, as summarized in Table 2. Framework that enables one to test the self-coordination of a swarm of controllers, aiming to solve the distributed optimal power flow algorithm in a DC network Queiroz et al, 2020 [26] Manufacturing system (tested in a real case study-automotive assembly line)…”
Section: Collective-intelligence-based Cps Approachesmentioning
confidence: 99%
“…Multi-agent systems-agents to manage the manufacturing line and report problems related to unexpected events In this analysis, most of the works use MAS-based approaches to provide the required collective intelligence in industrial CPS, particularly using distributed interaction strategies (e.g., negotiation mechanisms) to achieve collective intelligence, as presented in [23,24,30,32,33]. Complementary emergent digital technologies were also identified (e.g., IoT, edge, fog and cloud computing, and AI [26,28,31,34]), usually embedded in MAS solutions to empower data analysis and intelligence capabilities. It is interesting to note that these distributed intelligence capabilities are usually balanced among the edge/fog/cloud computational layers, exploring the benefits they provide to address the particularities of the different data analysis demands.…”
Section: Stadnicka Et Al 2020 [27]mentioning
confidence: 99%
See 1 more Smart Citation
“…Cooperation among multiple agents is necessary to dynamically construct collaborative groups for the completion of customized production tasks [118]. As discussed in Section IV, multiple agents with edge computing provide a better option than a single device to build a collaborative operation to realize CM [78], [119]. Therefore, by combining the edge computingassisted intelligent agents and different AI algorithms, a novel cooperative operation can be constructed as shown in Fig.…”
Section: A Cooperative Multiple Agentsmentioning
confidence: 99%
“…Some industries are willing to use these techniques and some SOHOMA articles describe applications of PDS via some case studies in the manufacturing industry [25], [26].…”
Section: 1mentioning
confidence: 99%